‘Interfaith Dialogue’ dan Hubungan Antaragama dalam Perspektif Islam - Syamsuddin Arif (Universitas Darussalam Gontor, 2010)
This article addresses issues related to the interfaith dialogue, focusing on the historical context from which it emerged and uncovering the tacit assumptions underlying the idea. It is argued that interfaith dialogue is part and parcel of the Christian mission which seeks to promote inclusivism but also eventually leads to pluralism and relativism. In addition, the article also discusses the three approaches taken by Muslims throughout centuries in dealing with people of other faiths. This article addresses issues related to the interfaith dialogue, focusing on the historical context from which it emerged and uncovering the tacit assumptions underlying the idea. It is argued that interfaith dialogue is part and parcel of the Christian mission which seeks to promote inclusivism but also eventually leads to pluralism and relativism. In addition, the article also discusses the three approaches taken by Muslims throughout centuries in dealing with people of other faiths. First approach is to call with wisdom and good advice (da‘wah bil hikmah wal mau‘izah alh asanah). The second is to argue with what better (jidal billati hiya ah san). And the last approach used is war.